THE BURDEN INTERVIEW. USEFULNESS AND VALIDITY OF THE BURDEN CONCEPT - Montorio Cerrato, Ignacio; Fernández de Trocóniz, María Izal; López López, Almudena; Sánchez Colodrón, María (Anales de Psicología / Annals of Psychology, 1998)
The purpose of this project was to identify the underlying dimensions of the burden concept just as it is assessed by The Burden Interview (Zarit and Zarit, 1983), as well as to set up the relationships between the identified dimensions and external criteria which are implied in the caregiving of functional dependent elderly. These processes of identification and analysis allowed to replace the burden concept into a wider conceptual framework. The sample consisted of 62 caregivers and 45 of their care-recipients. Besides the caregiver burden other variables were assessed, diferent aspects of burden stressors (time of caregiving, quality of the relationship between caregiver and care-recipient, functional capacity, mental state and behavioral problems of the care.recipient) and some of the effects of the caregiving situation on caregiver=s well-being (perceived health, use of the health system services, subjective satisfaction). Results showed diferent relationships between three underlying dimensions of caregiver=s burden (cargiving impact, interpersonal burden and autoeficacy expectatives) and some external criteria, revealing the multidimensional nature of the burden in the same way other researchers had pointed out. The analysis of these results and bearing in mind the theorical model of stress point out the necessity to overcome important theorical and methodological deficiencies of the burden concept.